Assessment of higher order thinking skills - Schraw, Gregory J.; Robinson, Daniel R. (Current perspectives on cognition, learning, and instruction., 2011)
This volume examines the assessment of higher order thinking skills from the perspectives of applied cognitive psychology and measurement theory. The volume considers a variety of higher order thinking skills, including problem solving, critical thinking, argumentation, decision making, creativity, metacognition, and self-regulation.Fourteen chapters by experts in learning and measurement comprise four sections which address conceptual approaches to understanding higher order thinking skills, cognitively oriented assessment models, thinking in the content domains, and practical assessment issues. The volume discusses models of thinking skills, as well as applied issues related to the construction, validation, administration and scoring of perfomancebased, selected-response, and constructed-response assessments.The goal of the volume is to promote a better theoretical understanding of higher order thinking in order to facilitate instruction and assessment of those skills among students in all K-12 content domains, as well as professional licensure and cetification settings.